Biocompatible and blood–brain barrier permeable carbon dots for inhibition of Aβ fibrillation and toxicity, and BACE1 activity. Issue 35 (29th August 2017) - Han, Xu; Jing, Zhifeng; Wu, Wei; Zou, Bing; Peng, Zhili; Ren, Pengyu; Wikramanayake, Athula; Lu, Zhongmin; Leblanc, Roger M.
Abstract : The blood–brain barrier permeable C-Dots can deactivate the BACE1 and further inhibit Aβ fibrillation and toxic oligomer formation. Abstract : Amyloid-β peptide (Aβ) fibrillation is pathologically associated with Alzheimer's disease (AD), and this has resulted in the development of an Aβ inhibitor which is essential for the treatment of AD. However, the design of potent agents which can target upstream secretases, inhibit Aβ toxicity and aggregation, as well as cross the blood–brain barrier remains challenging. In, this research carbon dots for AD treatment were investigated in vitro using experimental and computational methods for the first time. The results presented here demonstrate a novel strategy for the discovery of novel antiamyloidogenic agents for AD treatments.